Word-likeness ratings of English-like non-words by Arabic and Chinese learners of English: implications for assessing proficiency - Aljasser, Faisal M.; Wang, Yusen; Vitevitch, Michael S. (Frontiers in Language Sciences, 2025)
The present study investigated English learners' subjective word-likeness ratings of English-like non-words. For both native Arabic and Mandarin speakers learning English, the subjective word-likeness ratings correlated with objective phonotactic probability measures of those non-words. Although there were no differences between the subjective word-likeness ratings of Beginner and Advanced English learners, the word-likeness ratings of Beginner and Advanced learners did differ from the ratings provided (in a previous study) by native English speakers, suggesting that subjective ratings of phonotactic knowledge may be useful in measuring the extent to which phonological knowledge approaches native-like levels. The results of the present study underscore the important role of phonotactic knowledge in language proficiency. Implications of these findings to second language learning are discussed, with an emphasis on how the non-word rating task might be used as a novel and efficient method to assess one aspect of language proficiency.